Miary podobieństwa obiektów symbolicznych : miary de Carvalho - Dudek, Andrzej (Symbolic Objects Similarity Measures : De Carvalho Measures, 2006)
This paper presents main measures used for measuring similarity and dissimilarity between symbolic (e.g. not necessarily numeric) objects. This second part is a continuation of the article form Ekonometria XIV and describes de Carvalho dissimilarity measures along with definitions of comparison and aggregation functions, description potential of symbolic object with an example of using de Carvalho measures matrix as an input to Ward clustering algorithm.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 62-74